PENGARUH KOMPETENSI,INDEPENDENSI,DAN INTEGRITAS TERHADAP PENDETEKSIAN KECURANGAN DENGAN PELATIHAN AUDITOR SEBAGAI PEMODERASI - Silvya Sischa Yulia Putri; Taufeni Taufik; Aunurrafiq (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This study aims to determine The Effect Of Competence, Independence, And Integrity On Fraud Detection With Auditor Training As Moderation. The population in this study were all internal auditors at the Inspectorate of Riau Province. By using the census sampling method, which makes all members of the population a sample of 100 internal auditors with the data collection method using a questionnaire. Based on the results of the study, it shows that Competence, Independence, and Integrity Affect Fraud Detection at the Inspectorate of Riau Province. Meanwhile, with the moderation of Auditor Training, the Competency variable has no effect on Fraud Detection at the Inspectorate of Riau Province. This study has a contribution in improving the ability of internal auditors to detect fraud in the Inspectorate of Riau Province.